Mentoring of Hispanic Persons in Theological Education: Reflections on Distinctive Elements - Pazmiño, Robert W. (Didache: Journal of Christian Education, 2025)
Hispanic scholars are increasingly gaining seats at the table of theological education in the United States, yet many remain marginalised under it, seeking food and opportunities for advancement in academic institutions. This study examines the distinctive elements of mentoring Hispanics in theological education, exploring how cultural features and biblical foundations inform effective mentoring relationships within these communities. This research was conducted in the context of North American theological educational institutions, with particular attention to the emergence of Hispanic theological scholars and organisations such as AETH (Asociación para la Educación Teológica Hispana) and La Comunidad of Hispanic American Scholars of Religion. This research synthesises insights from educational theory, theological studies, and cultural analysis to develop a framework for understanding mentoring in Hispanic theological education. The investigation revealed eight distinctive cultural traits among Hispanics that inform mentoring relationships: passion, personalism, soul paradoxes, community, spiritual journey, musical elan, fiesta, and family. The study identifies parallels between traditional mentoring and the Hispanic concept of padrino/a (baptist parenting), showing how cultural understanding improves the effectiveness of mentoring. This study establishes that effective mentoring develops through four stages: idealisation, disappointment, differentiation, and partnership.